Dynamic Assessment and Its Implications for RTI Models - Wagner, Richard K.; Compton, Donald L. (Journal of learning disabilities, 2011)
Dynamic assessment refers to assessment that combines elements of instruction for the purpose of learning something about an individual that cannot be learned as easily or at all from conventional assessment. The origins of dynamic assessment can be traced to Thorndike (1924), Rey (1934), and Vygotsky (1962), who shared three basic assumptions. The first assumption is that conventional assessment does not work for children who have diverse educational and cultural experiences. The second assumption is that people should be interested more in where children can be tomorrow if given adequate education or intervention rather than in where children are now given their previous educational history. The third and final assumption is that the reason for assessment lies in intervention and, consequently, that the results of assessment should have direct implications for selecting or modifying interventions. Obvious parallels exist between fundamental assumptions of dynamic assessment and those of recent response-to-intervention (RTI) models (see Grigorenko, 2009, for a comprehensive and insightful recent comparison between dynamic assessment and RTI). RTI models can be used as the basis of service delivery and also as a source of assessment information. Arguments in support of using RTI models as a source of assessment information mirror the three key assumptions of dynamic assessment.